The Hydrogeochemical Stratigraphy of Brines and Its Implications on Water Management in the Central Jordan-Dead Sea Rift Valley, Israel. (17th December 2020) - Rosenthal, Eliahu; Möller, Peter; Buch-Leviatan, Orna; Politi, Moshe
Abstract : The exploratory borehole Megiddo-Jezre'el 1 (MJ1) was drilled in Israel, in the Bet She'an Valley which branches out from the Central Jordan Rift. It reached the depth of 5060 m and bottomed within the Upper Triassic Mohilla Fm. Following the increase of groundwater exploitation, the Cl - concentrations increased and ionic ratios changed indicating inflow of Ca 2+ -Cl - brines, the origins of which were hitherto unknown. Data from the new MJ1 borehole revealed that rock porosities decrease with depth. Lowermost values of about 3% were interpreted from logs in Lower Jurassic and Triassic strata. The highest shut-in pressures were measured in the Upper Jurassic sequence raising the water much higher than the ground surface. Along the drilled section, there is a continuous downward increase in Cl - concentrations in the range of 12-186 g Cl - /l and a very clear stratification of brines. Data from the MJ1 borehole and from other exploration wells indicate that in the subsurface of the area, there are two definite source brines: Triassic brine and the Late Tertiary (so-called) Rift brine. Brines encountered in Jurassic and Cretaceous beds represent ancient mixtures of the two source brines involving various water-rock chemical transformations. Evidence of very high pressures in deep boreholes Devora 2A, Rosh Pinna 1, and MJ1 revealed the existence of a mechanism in which the deep brines are "piston-driven" upwards and possibly also laterally. The ongoing salinization of groundwater in the area is due to the inflow of the Late Tertiary Ca 2+ -Cl - Rift brines and not that of the Jurassic or Triassic brines. The hydrogeological and hydrochemical data from borehole MJ1 is of major importance for the management of groundwater resources in the Central Jordan Rift Valley and in the adjacent geologically connected areas.